Downregulation of miR-33a-5p in Hepatocellular Carcinoma: A Possible Mechanism for Chemotherapy Resistance - Meng, Wei (Med Sci Monit, 2017)
BACKGROUND: Multi-drug resistance is one of the major problems limiting the efficacy of cisplatin (CDDP) in treatment of hepatocellular carcinoma (HCC), and abnormal microRNA (miRNA) expression in drug-resistant cell lines plays an important role in liver cancer chemotherapy resistance. MATERIAL/METHODS: We established stable Hep3B and 97L HCC cell strains resistant to CDDP, both in vitro and in vivo. A combination of microRNA microarray and RT-qPCR experiments were used to screen differentially expressed miRNAs in HCC cell strains. A CCK-8 assay was carried out to detect and calculate the survival rates and relative inhibitory rates. Oligonucleotide transfection was used to confirm the regulatory function of the miRNA in HCC drug resistance. RESULTS: The IC50 of Hep3B/CDDP(v), 97L/CDDP(v), Hep3B/CDDP(s), and 97L/CDDP(s) were significantly higher than that of their parental cells. Moreover, the doubling time of drug-resistant cells increased compared with their parent cells. MiRCURYTM LNA Array (v 16.0) high-throughput tests of resistant cell models and their parent cells showed that there were 5 downregulated microRNAs in the 4 drug-resistant cell lines, and we chose hsa-miR-33a-5p as our target for further study. Oligonucleotide transfection showed that miR-33a-5p overexpression increased the cisplatin sensitivity of Hep3B/CDDP(v) and 97L/CDDP(v) drug-resistant cells and reduced their resistance. Additionally, inhibition of miR-33a-5p expression reduced cisplatin sensitivity in Hep3B and 97L and increased their drug resistance. CONCLUSIONS: This study confirmed that the most downregulated microRNA, miR-33a-5p, can mediate the cisplatin resistance of HCC cells, providing a new and feasible direction for research into combatting liver cancer chemotherapy resistance.